En busca de Próspero: Pedro Henríquez Ureña interpreta Ariel - Cesana, Raffaele (El Colegio de México, 2023)
This article analyses the important role the essay Ariel (1900), written by José Enrique Rodó, played in the work of Pedro Henríquez Ureña.Whilst it focusses on the interpretation of the critical essay “Ariel. La obra de José Enrique Rodó” that the Dominican humanist published in the journal Cuba Literaria (1905), it covers the wider period from 1900 to 1911, which was the most intense phase in his reception of Rodo’s ideas. The aim of this paper is to show how Henríquez Ureña’s early interpretation of these ideas was constantly changing as —is his historiographical studies, his philological research and his work as a teacher— he went in search of what he was to call our American expression.